Semantic and Pragmatic Features of Euphemisms in German and Uzbek Media Discourse - Nurkulov, Javlon Rashid ugli (The Lingua Spectrum, 2026)
In the article, a comparative analysis of the semantic and pragmatic features of euphemisms in German and Uzbek media discourse is conducted. Online newspaper texts are used as the primary research material, and the functional potential of euphemistic units in political, economic, and social contexts is examined. The results of the analysis show that euphemisms perform the functions of softening information, neutralizing negative and harsh content, and ensuring communicative caution. Euphemisms in German and Uzbek media discourse are widely used across political, economic, and social domains, which is illustrated through examples. Furthermore, functional similarities and cultural-stylistic differences between the two languages are identified. The research findings demonstrate that pragmatic and cultural factors play an important role in the translation of euphemisms and highlight the necessity of accurate contextual interpretation in media discourse. Overall, euphemisms serve as an important linguistic tool in media discourse, contributing to the reduction of emotional impact and the softening of social communication. This approach enables a deeper understanding of the pragmatic potential of linguistic means in media texts and helps to identify their socio-communicative functions. The results are scientifically generalized, final conclusions are drawn, and their practical significance is indicated.